The Use of Chatgpt as a Tool to Facilitate Writing Scientific Work - Salman Yafi (Yayasan Adra Karima Hubbi, 2024)
This research aims to explore the use of ChatGPT as a tool in scientific writing, given the challenges in academic writing such as difficulties in finding references, organizing arguments, and formulating ideas systematically. By utilizing a qualitative approach through a literature study, this research analyzes the effectiveness of ChatGPT in increasing writing efficiency, overcoming difficulties in developing ideas, and improving the quality of arguments. The results show that ChatGPT is able to speed up drafting, summarize literature, and provide relevant revision suggestions, although it still requires manual verification to prevent plagiarism and misinformation. The implications of this study highlight the potential of ChatGPT as a support tool in academia, with recommendations for ethical and optimal integration of this technology in education.